Migrant Revolutions: Haitian Literature, Globalization, and U.S. Imperialism - Kaussen, Valerie (Lexington Books, 2007)
Migrant Revolutions: Haitian Literature, Globalization, and U.S. Imperialism interprets Haitian literature in a transnational context of anti-colonial_and anti-globalization_politics. Positing a materialist and historicized account of Haitian literary modernity, it traces the themes of slavery, labor migration, diaspora, and revolution in works by Jacques Roumain, Marie Chauvet, Edwidge Danticat, and others. Author Valerie Kaussen argues that the sociocultural effects of U.S. imperialism have renewed and expanded the relevance of the universal political ideals that informed Haiti's eighteenth-century slave revolt and war of decolonization. Finally, Migrant Revolutions defines Haitian literary modernity as located at the forefront of the struggles against transnational empire and global colonialism.